PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DALAM PELAYANAN SURAT KETERANGAN PINDAH DI KECAMATAN BUNGARAYA KABUPATEN SIAK TAHUN 2018 - Khoiriyah, Miftakul; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Integrated District Administration Service (PATEN) written in the Minister of Home Affairs (PERMENDAGRI) regulation Number 4 of 2010 is the organizer of public services in the Subdistrict from the application stage to the stage of publication of documents in one place. The purpose and objective of the Integrated District Administration Service is to make the Subdistrict a community service center that embodies the service node for the One Stop Integrated Service Agency / Offic               This research study uses analytical methods on public service theory. This study uses a type of qualitative research. Data analysis unit with interviews with several speakers, with primary and secondary research data               The results of the research are the Implementation of Integrated District Administrative Services (PATEN) in Moving Certificate Services in Bungaraya District in accordance with the Minister of Home Affairs regulation number 4 of 2010. For service time in Bungaraya Subdistrict, it applies according to the type of each service, while costs Community service does not need to incur any costs in performing services in the Bungaraya District office. But in Bungaraya Subdistrict still has shortcomings including the number of service personnel who are still minimal and infrastructure facilities that still need to be added again. The communication factor runs effectively in the District office as well as the disposition factor and organizational structure where from these factors really greatly affect the implementation of PATEN in the office, it is different from the natural resources factor, especially HR which still lacks the implementation of services in Bungaraya District office Keywords: PATEN, Implementation and Service